Pendidikan Islam Di Era Globalisasi - Muhammad Habibirrahim; Akramul Insan Zaer; Fadhilatul Muharram; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The globalization that has occurred today has given rise to various changes in human life. The change creates opportunities and challenges, both in education, politics, religion and even socio- culture. To face the opportunities and challenges that human beings are required to increase his resources. Education is the right means, in addition to producing superior human, kratif, caterpillar, diligent, also sustained by to the faith.